Britishness and Muslim-ness: differentiation, demarcation and discrimination in political discourse. Issue 2 (December 2015) - Allen, Chris
Abstract : The Britishness agenda found in political speeches, reporting and opinion editorials is here posited as a form of 'new racism', as it emphasises the difference between 'them', Muslims, and 'us', non-Muslim Britons, and uses that difference as a defining demarcation. Twenty-first-century political discourse invested in the Britishness agenda works to eradicate distinctions between British Muslims and non-British Muslims, and even the distinction between those guilty of terrorist atrocities and those who have nothing to do with them. Muslims are framed within this discourse as the problem within multiculturalism, and the problem with multiculturalism. The difficulty of a demand to 'be more British' is laid bare.